CONCEPT OF MEDICAL AND PHARMACEUTICAL CARE FOR MYOCARDIAL INFARCTION AS A PROSPECTIVE FORM OF SERVICE TO THE POPULATION - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Николай Владимирович Абрамов; Виктор Андреевич Семенихин (Медицина в Кузбассе, 2021)
The review is devoted to topical problems of the development of the concept of pharmaceutical care and the interaction of pharmaceutical workers and representatives of medical organizations in the optimization of medical and pharmaceutical care in the process of treating the population with myocardial infarction. The importance of pharmaceutical care is shown, allowing to achieve results that improve the quality of life of a patient with myocardial infarction.